Reflections on the separation of powers and the normative function of the Superior Electoral Court (Revista do Tribunal Regional Federal da 3ª Região, 2023)
This article presents reflections on the regulatory power of the Electoral Justice and its normative function, especially of the Superior Electoral Court, in conjunction with the principle of separation and harmony between powers. To this end, the study starts from the definition of legal concepts, with a view to bibliographical research, with subsequent verification of acts of the Superior Electoral Court, decisions of the Federal Supreme Court, in addition to reference to the processing of legislative projects involving the electoral theme. From the analysis of relevant cases, we seek to consider the criticisms regarding the more active role of the Electoral Justice to give rise to debates about possible excesses in the exercise of its normative function, which could substantiate a possible violation of the rule of law.
Keywords: Electoral Justice; Normative function; Separation of powers; Rule of Law